(untitled) (Proceedings of International Educators Conference, 2023)
In the "Explanatory Dictionary of Pedagogy", the concept of "independent cognitive activity" is considered as a form of education aimed at strengthening the skills to be acquired, learning additional material. At the same time, the concepts of "Independent cognitive activity", "Self-education", "Improving independent cognitive activity" are used in scientific and educational literature as synonyms. During the observation of the educational activities of the students studying in the higher education system, it was found that the improvement of independent cognitive activity is considered to be a motivating force, a conscious interest, and an arousing force. Conscious interest is the most important indicator of independent activity, a high level. This is due to the level of skill of the teachers teaching mathematics, and students are interested in this or that subject or professional specialty.